Association between ABO blood groups and the risk of infection with SARS-CoV-2 in Iraq. Issue 11 (November 2022) - Hussein, Abdulhakeem D; Bakr, Ekhlas Aziz; Al-Jumaili, Mohammed Hadi Ali
Objective: The primary goals of this research were to analyze the relationship between ABO blood types and the severity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and investigate the effect of vaccination in Iraq. Methods: Data and outcomes were gathered from the medical records of 200 patients. Patients were categorized by blood group and vaccination status in the analysis. Results: In total, 200 hospitalized patients (125 men and 75 women) with confirmed SARS-CoV-2 infection and blood group (ABO) and clinical data were enrolled. Of the 200 patients, 155 (77.5%) were vaccinated against SARS-CoV-2. The results illustrated that 25 patients died, which might have been attributable to a lack of vaccination or older age. Our analysis revealed that blood group O individuals were much less likely to be infected by SARS-CoV-2 than non-O subjects, whereas blood group A individuals carried a higher risk of infection. Conclusions: Our findings illustrated that immunization significantly reduces COVID-19 risk across all age groups, but there has been an increase in the number of cases because of decreased vaccine efficacy in older patients and persons with comorbidities. However, 45% vaccination coverage lowered the outbreak's peak.